Expanding the footnote: how minor methodological decisions have impactful consequences for developmental results - Kucker, Sarah C.; Lorenz, Megan G. (Frontiers in Developmental Psychology, 2025)
Over the last quarter century, there has been an increased emphasis on taking a systems approach to development, especially considering possible mechanisms and non-obvious, often ignored factors driving children's behavior. Although this work has given us greater insight into the mechanisms behind developmental outcomes, considerably less focus has been given to the methodological choices researchers make along the way (at times, leaving some of those decisions at the level of a footnote). However small, these methodological choices impact the validity of our data and thus, the conclusions we can draw from developmental studies. The current manuscript expands on one such choice—that of stimuli—to highlight how the everyday decisions researchers make about the objects and contexts we use in a study may have larger cascading effects than what is anticipated. We use stimuli used in language development studies as an example case. As part of this argument, we review individual bodies of research exploring how salience, typicality, and presentation context of stimuli may uniquely influence children's behavior and subsequently the results in word learning research. We argue that in order for the field of development science to advance and for us to further a holistic understanding of developmental processes and mechanisms, the next steps must consider these often ignored factors and methodological choices.